A Review of Organic Food Consumption from a Sustainability Perspective and Future Research Directions (International Journal of Management and Sustainability, 2018)
This paper reviews organic food consumption from a sustainability perspective with a view to suggesting future research directions. It gives an overview of historical evolution of organic food consumption as a sustainability movement and provides a critical review of a large body of previous research, which examines organic food consumption from various perspectives. The paper highlights some research gaps and suggests essential future research directions in the field of study: (1) a discourse analysis of the notion of organic food; (2) a systematic industry review of the multiple organic food certification systems; (3) a comparative study to examine consumers’ confusion between scientifically proven health benefits of organic food and perceived value of organic food; (4) an examination of socio cultural aspects of organic food consumption; (5) an assessment of how the benefits of developing organic food markets transfer to developing countries and; (6) a development of a detailed profile of global consumers in the organic food market.